G114(P) Maternal Levels of Endosulphan in relation to Small-for-Gestational-Age Birth. (7th April 2014) - Dewan, P; Jain, V; Banerjee, BD; Gupta, P
Abstract : Aims and objectives: We conducted this study to look for a possible association between the blood levels of endosulphan (an organochlorine pesticide) in mothers and birth size of their offsprings, in a case-control design. Secondary objectives were to ascertain the transplacental and transmammary transmission of endosulphan by correlating maternal endosulphan levels with those in cord blood and breastmilk, respectively. Methods: This study was conducted in a tertiary hospital in Delhi, India. Participants included 30 term, small-for-gestational-age neonates and their mothers (Cases) and 30 term, appropriate-for-gestational-age neonates and their mothers (Controls). Women with known risk factors for intra-uterine growth retardation i.e., age <18 or > 35 y; malnutrition; chronic illnesses; substance abuse; and third trimester complications, and neonates with congenital malformations and multiple gestation were excluded. Endosulphan levels were estimated in maternal blood, cord blood, and breastmilk using gas-liquid chromatography. Maternal endosulphan levels were correlated with the birth size (neonatal weight, length, head circumference, mid arm circumference and chest circumference) as continuous variable. Linear regression analysis was used to ascertain the transplacental (correlation between maternal blood and cord blood pesticide levels) and transmammary (correlation between maternal blood and breastmilk pesticide levels) transmission of endosulphan. Results: Mothers in both groups had similar demographic characteristics while the infants in the case group were significantly smaller than those in the control group (Table 1). The mean (SD) concentration (ng/mL) of endosulphan in the maternal blood; cord blood; and breastmilk samples in both the groups were comparable (P > 0.05) (Table 2). No association between endosulphan levels in maternal blood, cord blood and breastmilk with the birth size was noted (Table 3). There was significant transplacental transfer of endosulphan (R=0.92, P < 0.001). The endosulphan levels in breastmilk were much higher than those in maternal blood. However, the correlation between maternal blood and breastmilk endosulphan levels was statistically insignificant (R=–0.255, P = 0.05). Conclusion: Endosulphan residues in mothers were not associated with the birth size of the newborns in our population. This may have been due to low exposure to endosulphan of populations residing in the Delhi region. Endosulphan residues were selectively partitioned in breastmilk thereby posing a risk of continued transmission to infants.